SOCIAL SELF-DETERMINATION OF A SECONDARY SCHOOL STUDENT IN THE CONTEXT OF HUMANIZATION OF THE EDUCATIONAL PROCESS - Aliyev, Roman; Chekhlov, Mikhail; Chehlova, Zoja; Keviša, Ingrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
We regard the social self-determination of senior secondary school students as the basis for their education as citizens of Latvia and citizens of Europe. This underpins the need to actualize the problem of social self-determination. The aim of the research is to determine the essence and structure of social self-determination of senior secondary school students and to identify the conditions for the development of social self-determination in secondary school students in the process of education. Research methods include observation, questionnaire, survey, comparison, experiment, and mathematical statistics. Research results are the following:- as a result of the study, there was determined the content and structure of social self-determination as a systemic personal formation, representing the relationship of two components: citizenship and intercultural identity; - the conditions for the development of social self-determination have been identified, including the humanization of the educational process based on a certain system of moral values and beliefs; -  the key strategy for organizing the educational process has been suggested: changing the content of education by introducing a cultural component, which would contribute to a change in all structural components, from the goal to the result; - this implies a change in the procedural aspect of education: the organization of a personal cultural dialogue; the dialogue is regarded as the basis for communication in the pedagogical process; - the key values of secondary school students were determined in the process of a fact-finding experiment.